Dylematy moralne polskich aptekarzy - Grychtoł, Anna (Annales. Etyka w Życiu Gospodarczym, 2015)
A comprehensive work that would be focused on the moral dilemmas of the pharmacistshas not been published yet. The pharmacist profession is commonly perceivedas an occupation associated with such virtues as calmness, precision andaccuracy. However, there is a lack of knowledge on the moral dilemmas the pharmacistcontends with. One of the reasons lies in the fact that some citizens of ourcountry, especially the younger generation, do not recognise the difference betweenthe profession of pharmacist and the profession of salesperson. On the other hand, asM. Brazier indicates, the majority of scientific works are almost exclusively concentratedon the ethical dilemmas of ‘high drama’ and ‘low incidence’. In that contextthe work of pharmacist appears to be imbued with the ‘small dramas’ taking placeevery day. Therefore, it seems to be necessary to point out what duties or conflicts ofvalues the Polish pharmacist faces and to make an attempt to find appropriate waysto solve them.